Current status of ovarian cancer surgical management. Argument for centralisation of care in Australia. (31st May 2018) - Carter, Jonathan; Pather, Selvan; Nascimento, Marcelo
Abstract : In Australia, ovarian cancer remains the most common cause of death among all the gynaecological malignancies, largely due to the fact that patients present at an advanced stage. Cytoreductive surgery has for a number of decades been the cornerstone of initial treatment for patients with advanced disease, where a smaller volume of residual disease (optimal cytoreduction) results in an improved outcome. Evidence indicates that optimal cytoreduction is best achieved by a certified gynaecological oncologist, and that subsequent management by a dedicated multidisciplinary team (MDT) results in patients more likely to receive 'evidenced based guideline care' and be offered participation in clinical trials. Patients managed by an MDT have been shown to have improved survival, their care to be cost effective and that they experience a high level of satisfaction and improved quality of life. Centralisation of care for patients with ovarian cancer should be considered gold standard care.